2022
DOI: 10.22159/ijap.2022v14i2.43658
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Pegylated Capecitabine Liposomal Formulations With Anticancer Activity Towards Colon Cancer

Abstract: Objective: Capecitabine is widely used in colorectal cancer treatment and has first-pass metabolism problem. Despite of its promising anticancer potential, capecitabine has not been used due to its poor solubility in water. The purpose of this study was to develop colon targeting capecitabine loaded stealth liposomes, which is a promising technique to avoid first-pass metabolism to achieve the desired bioavailability profile, increased water solubility and sustained release. Methods: Thin film hydration method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Particle size, zeta potential and PDI were measured using an Anton Paar Litesizer 500(Malvern instrument, UK) at a scattering angle of 90 °C. The diluted dispersion was placed in a polystyrene cuvette with a path length of 10 mm and allowed to equilibrate for 120 seconds [22].…”
Section: Analysis Of Particle Size Zeta Potential and Polydispersity ...mentioning
confidence: 99%
“…Particle size, zeta potential and PDI were measured using an Anton Paar Litesizer 500(Malvern instrument, UK) at a scattering angle of 90 °C. The diluted dispersion was placed in a polystyrene cuvette with a path length of 10 mm and allowed to equilibrate for 120 seconds [22].…”
Section: Analysis Of Particle Size Zeta Potential and Polydispersity ...mentioning
confidence: 99%
“…On the basis of earlier reported literature higher concentrations of cholesterol and surfactants tween 80 and span 60 the rate drug entrapment was higher whereas at lower concentrations it was decreased. 26,27 Additionally, psoriasis is characterized by the release several cytokines such as interferon-γ, TNF-α and the number of interleukins involved in the inflammation are followed by infiltration of immune cells into the skin and finally hyperkeratosis. In-vivo antipsoriatic activity was evaluated on basis of PASI scorings along with primary dermal irritation study.…”
Section: Effect Of Cpg3 On Proinflammatory Cytokines In Imiquimod Ind...mentioning
confidence: 99%
“…The swelling index was calculated using the equation provided. [25][26][27] In-vitro release study The purpose of this study was to employ the USP type II dissolution test apparatus to calculate the buccal tablet release rate in-vitro. Medicine in tablets is often released from just one side.…”
Section: Swelling Indexmentioning
confidence: 99%
“…The infrared (IR) spectrum analysis suggested that no significant interaction between the drug and the excipients was detected (Figure 1). [26][27][28][29][30][31] Pre-compression Study Table 2 displays the outcomes of the pre-compression parameters. The bulk density and tapped density measurements were observed to fall within acceptable limits, suggesting that the packaging qualities necessary for compression are satisfactory across all formulations.…”
Section: Compatibility Studymentioning
confidence: 99%